Antifouling coating composition

KR103036911B1Active Publication Date: 2026-10-21CHUGOKU MARINE PAINTS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020210037368
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-23
Publication Date
2026-10-21
Estimated Expiration
2041-03-23

Smart Images

  • Figure 112021034038173-PAT00001
    Figure 112021034038173-PAT00001
  • Figure 112021034038173-PAT00002
    Figure 112021034038173-PAT00002
  • Figure 112021034038173-PAT00003
    Figure 112021034038173-PAT00003
Patent Text Reader

Abstract

The present invention aims to provide an antifouling paint composition capable of forming an antifouling film that achieves both long-term antifouling properties and crack resistance in seawater and freshwater. To solve the above problem, the antifouling paint composition of the present invention contains a silyl ester-based polymer (A), a copolymer (B) having a structural unit (b-1) derived from styrene, and a structural unit (b-2) derived from a polymerizable monomer (b2) represented by formula (b2). Formula (b2): CH2 = CH-COO-(Rb1-O)n-Rb2 [In formula (b2), Rb1 is an alkanediyl group having 1 to 5 carbon atoms, Rb2 is an alkyl group having 1 to 5 carbon atoms, and n is an integer from 1 to 3.]
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an antifouling paint composition, an antifouling film, a substrate to which the antifouling film is attached, and a method for manufacturing a substrate to which the antifouling film is attached. Background Technology

[0002] Various types of aquatic organisms are prone to attaching to the surfaces of materials (such as ships, underwater structures, fishing nets, and seawater supply and drainage pipes in factories) that are exposed to water (oceans, rivers, lakes, and swamps, etc.) for extended periods in natural environments. When aquatic organisms attach to the surface of a material, they can damage its appearance or cause various problems. For example, if the material is a ship, increased resistance due to water currents may lead to a decrease in ship speed and an increase in fuel consumption. If the material is an underwater structure, damage to the anti-corrosion coating applied to the surface may result in reduced strength and functionality, as well as a significant shortening of its lifespan. If the material is a fishing net, such as aquaculture nets or fixed nets, the mesh may become clogged by aquatic organisms, causing serious problems such as acid deficiency and death of farmed or caught organisms. If aquatic organisms attach to and proliferate in the seawater supply and drainage pipes of factories, thermal and nuclear power plants, etc., it can cause blockage of the pipes or a decrease in water flow velocity.

[0003] To prevent the attachment of aquatic organisms that cause such problems, it is common practice to form an antifouling film by applying an antifouling paint to the surface of a substrate. Among these antifouling paints, hydrolytic antifouling paints are widely used due to advantages such as their ability to exhibit excellent antifouling performance, and as one such example, the development of antifouling paints containing silyl ester-based polymers has been underway.

[0004] Patent Document 1 describes an antifouling paint composition in which a copolymer comprising structural units derived from styrene and structural units derived from glycidyl (meth)acrylate is incorporated into an antifouling paint containing a silyl ester-based polymer.

[0005] Patent document 2 describes an antifouling paint composition that forms a self-polishing and antifouling coating by mixing an organosilyl copolymer and a (meth)acrylate polymer that is incompatible with the copolymer and phase-separable.

[0006] Patent document 3 describes an antifouling paint composition comprising a polymeric plasticizer consisting of an ethylenically unsaturated carboxylic acid ester polymer having a glass transition temperature of -20°C or lower and a number average molecular weight of 500 to 20,000, and a (meth)acrylic acid triorganosilyl copolymer. Prior art literature

[0007] International Publication No. 2014 / 175246; Japanese Patent Publication No. 2006-503115; International Publication No. 2008 / 105122 The problem to be solved

[0008] There is a problem in that a coating film containing a silyl ester-based polymer dissolves at a normal rate in seawater for a certain period from the beginning of immersion, but as time passes, hydrolysis proceeds within the coating film, causing a decrease in water resistance and resulting in cracks or peeling. Regarding this problem, when an acrylic copolymer is incorporated into the silyl ester-based polymer, the crack resistance of the coating film improves, while the antifouling resistance often decreases. Although these problems have been examined in Patent Documents 1 to 3, there was room for further improvement regarding the compatibility of long-term antifouling resistance and water resistance of the coating film.

[0009] The objective of the present invention is to provide an antifouling paint composition capable of forming an antifouling film that achieves both long-term antifouling properties and crack resistance in seawater and freshwater. means of solving the problem

[0010] The inventors have conducted diligent research to solve the above problem and have discovered that the antifouling paint composition described below can solve the above problem. That is, the present invention relates to [1] to

[15] below.

[0011] [1] An antifouling paint composition comprising a silyl ester-based polymer (A), a copolymer (B) having a structural unit (b-1) derived from styrene and a structural unit (b-2) derived from a polymerizable monomer (b2) represented by formula (b2).

[0012] Equation (b2): CH2 = CH - COO - (R b1― O) n― R b2

[0013] [Equation (b2), R b1 is an alkanedial group having 1 to 5 carbon atoms, and R b2 is an alkyl group having 1 to 5 carbon atoms, and n is an integer from 1 to 3.

[0014] [2] An antifouling paint composition described in [1], wherein the proportion of the structural unit (b-1) in the copolymer (B) is 30 to 80 mass%.

[0015] [3] An antifouling paint composition described in [1], wherein the proportion of the structural unit (b-2) in the copolymer (B) is 15 to 45 mass%.

[0016] [4] An antifouling paint composition described in [1], wherein the proportion of the structural unit (b-1) in the copolymer (B) is 30 to 80 mass% and the proportion of the structural unit (b-2) is 15 to 45 mass%.

[0017] [5] An antifouling paint composition described in any one of [1] to [4], wherein the polymerizable monomer (b2) represented by formula (b2) is an alkoxyalkyl acrylate.

[0018] [6] An antifouling paint composition described in [5], wherein the polymerizable monomer (b2) represented by formula (b2) is 2-methoxyethyl acrylate.

[0019] [7] An antifouling paint composition described in any one of [1] to [6], wherein the above silyl ester-based polymer (A) has a structural unit derived from triisopropylsilyl methacrylate.

[0020] [8] An antifouling paint composition described in any one of [1] to [7], wherein the mass ratio (A:B) of the above silyl ester-based polymer (A) and the above copolymer (B) is 90:10 to 30:70.

[0021] [9] An antifouling paint composition described in any one of [1] to [8], further containing a monocarboxylic acid compound (C).

[0022]

[10] An antifouling paint composition described in any one of [1] to [9], further containing copper and / or a copper compound (D).

[0023]

[11] An antifouling paint composition described in any one of [1] to

[10] , further containing an organic antifouling agent (E).

[0024]

[12] An antifouling film formed from any one of the antifouling paint compositions [1] to

[11] above.

[0025]

[13] A substrate and a substrate having an antifouling film as described in

[12] installed on the surface of the substrate.

[0026]

[14] The above-described antifouling coating material is one or more selected from ships, underwater structures, fishing materials and water supply and drainage pipes.

[13] The above-described antifouling coating material.

[0027]

[15] A method for manufacturing a substrate with an antifouling film attached, comprising the process of applying or impregnating the antifouling paint composition described in any one of [1] to

[11] above onto the substrate. Effects of the invention

[0028] According to the present invention, an antifouling paint composition capable of forming an antifouling film that can achieve both long-term antifouling properties and crack resistance of the film in seawater and freshwater can be provided. Specific details for implementing the invention

[0029] The embodiments of the present invention are described in detail below.

[0030] Each component described in this specification may be used in one or two or more types.

[0031] The term "polymer" is used to include homopolymers and copolymers.

[0032] "(Meta)acrylate" is a general term for acrylates and methacrylates. The same applies to usages regarding (meth)acrylic acid, etc.

[0033] "Structural unit derived from XX" means that XX is A 1 A 2 C = CA 3 A 4 (C=C is a polymerizable carbon-carbon double bond, and A 1 ~A 4 If represented as (each an atom or group bonded to a carbon atom), it is a structural unit expressed by, for example, the following formula.

[0034]

[0035] [Antifouling paint composition]

[0036] The antifouling paint composition of the present embodiment (hereinafter also referred to as “Composition (I)”) contains a silyl ester-based polymer (A), a copolymer (B) having a structural unit (b-1) derived from styrene, and a structural unit (b-2) derived from a polymerizable monomer (b2) represented by the formula (b2) described below.

[0037] <Silyl ester-based polymer (A)>

[0038] A silyl ester-based polymer (A) (hereinafter also referred to as “polymer (A)”) is a polymer having a structural unit derived from a silyl ester-based monomer. Preferably, the polymer (A) has a structural unit (a-1) derived from a polymerizable monomer (a1) represented by formula (a1).

[0039]

[0040] Each symbol in equation (a1) is explained below.

[0041] R 1 It is a hydrogen atom or a methyl group, preferably a methyl group.

[0042] R 2 ~R 6 Each is a monovalent organic group having 1 to 20 carbon atoms that may independently have a heteroatom. Examples of the above organic groups include straight-chain or branched alkyl groups, cycloalkyl groups, and aryl groups in which a heteroatom such as an oxygen atom may be interposed between the bonds of carbon atoms. In terms of easily obtaining an antifouling film with balanced long-term antifouling properties and water resistance (cracking resistance) having appropriate hydrolytic properties, it is preferably one or more selected from straight-chain or branched alkyl groups having 1 to 8 carbon atoms and phenyl groups, and more preferably a branched alkyl group.

[0043] Examples of straight-chain or branched alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, t-butyl, pentyl, hexyl, and 2-ethylhexyl groups, and preferably isopropyl groups.

[0044] n is an integer greater than or equal to 0 or 1, preferably 0. The upper limit of n may be, for example, 50.

[0045] X is a hydrogen atom or R 7 It is a group represented by ―O―C(=O)―, and preferably a hydrogen atom. R 7A hydrogen atom, a monovalent organic group having 1 to 20 carbon atoms that may have heteroatoms, or R 8 R 9 R 10 It is a silyl group represented by Si. R 8 , R 9 and R 10 Each is a monovalent organic group having 1 to 20 carbon atoms that may independently have a heteroatom. Specific examples of monovalent organic groups having 1 to 20 carbon atoms that may have a heteroatom can be given as described above.

[0046] As the polymerizable monomer (a1), trialkylsilyl(meth)acrylate, alkyldiarylsilyl(meth)acrylate and aryldialkylsilyl(meth)acrylate are preferred, and trialkylsilyl(meth)acrylate is more preferred. Examples of trialkylsilyl(meth)acrylate include trimethylsilyl(meth)acrylate, triethylsilyl(meth)acrylate, tripropylsilyl(meth)acrylate, triisopropylsilyl(meth)acrylate, tributylsilyl(meth)acrylate, triisobutylsilyl(meth)acrylate, tri-sec-butylsilyl(meth)acrylate, tri-2-ethylhexylsilyl(meth)acrylate, and butyldiisopropylsilyl(meth)acrylate. In addition, as a polymerizable monomer (a1), polymerizable monomers such as 1-(meth)acryloyloxynonamethyltetrasiloxane, in which n is 2 or more in the above formula (a1), may be cited. Among these, trialkylsilyl(meth)acrylate having branched alkyl groups is preferred, triisopropylsilyl(meth)acrylate is more preferred, and triisopropylsilylmethacrylate is particularly preferred, from the viewpoint that a nonfouling film having appropriate hydrolytic properties and excellent long-term nonfouling properties and water resistance (cracking resistance) can be easily obtained.

[0047] The structural unit (a―1) may be of one type or two or more types.

[0048] The polymer (A) may additionally have a structural unit (a-2) derived from another ethylenically unsaturated monomer (hereinafter also referred to as “monomer (a2)”).

[0049] As for the monomer (a2), for example,

[0050] (Meta)acrylic acid;

[0051] (Meth)acrylic acid esters, specifically, alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3,5,5-trimethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, and stearyl (meth)acrylate; and aliphatic (meth)acrylates such as cyclohexyl (meth)acrylate. Ring-containing (meth)acrylates; aromatic ring-containing (meth)acrylates such as phenyl(meth)acrylate, benzyl(meth)acrylate, etc.; hydroxyalkyl(meth)acrylates such as hydroxymethyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, etc.; methoxymethyl(meth)acrylate, 2-methoxyethyl(meth)acrylate, ethoxymethyl(meth)acrylate, 2-ethoxyethyl(meth)acrylate, 4-methoxybutyl(meth)acrylate, methoxypropyl(meth)acrylate, ethoxypropyl(meth)acrylate, Alkoxyalkyl (meth)acrylates or aryloxyalkyl (meth)acrylates such as propoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, isobutoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; glycol-based (meth)acrylates such as ethoxy-diethylene glycol (meth)acrylate, methoxy-triethylene glycol (meth)acrylate, and methoxy-dipropylene glycol (meth)acrylate;

[0052] Vinyl monomers, specifically, vinyl acetate, isobutyl vinyl ether, styrene, vinyltoluene, (meth)acrylonitrile, vinyl propionate, vinyl benzoate;

[0053] (Meth)acrylates containing metal ester groups, specifically, zinc (meth)acrylate, zinc di(meth)acrylate, copper (meth)acrylate, and copper di(meth)acrylate.

[0054] ...can be cited.

[0055] The structural unit (a―2) may be of type 1 or type 2 or more.

[0056] The proportion of structural units (a-1) in the polymer (A) is preferably 35 mass% or more, more preferably 40 mass% or more, even more preferably 45 mass% or more, preferably 80 mass% or less, more preferably 75 mass% or less, and even more preferably 70 mass% or less.

[0057] The proportion of structural units (a-2) in the polymer (A) is preferably 20 mass% or more, more preferably 25 mass% or more, even more preferably 30 mass% or more, preferably 65 mass% or less, more preferably 60 mass% or less, and even more preferably 55 mass% or less.

[0058] If the ratio of each structural unit is within the above range, the antifouling film formed from composition (I) has appropriate hydrolytic properties and tends to have excellent antifouling properties over a long period. The ratio of each structural unit can be determined by NMR (Nuclear Magnetic Resonance Spectroscopy), Pyro-GC / MS (Pyrolytic Gas Chromatography Mass Spectrometry), etc.

[0059] The weight average molecular weight (Mw) of the polymer (A) is preferably 3,000 or more, more preferably 10,000 or more, preferably 70,000 or less, more preferably 50,000 or less, in order to improve the crack resistance of the antifouling film formed from the composition (I). Mw can be obtained by gel penetration chromatography (GPC) measurement under the conditions employed in the examples described below or by an equivalent method.

[0060] One or more types of polymer (A) may be used.

[0061] <Copolymer (B)>

[0062] The copolymer (B) has a structural unit (b-1) derived from styrene and a structural unit (b-2) derived from a polymerizable monomer (b2) represented by formula (b2).

[0063] Equation (b2): CH2 = CH - COO - (R b1 ―O) n ―R b2

[0064] In equation (b2), R b1 is an alkanedyl group having 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms, and R b2 is an alkyl group having 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms, and n is an integer of 1 to 3, preferably 1.

[0065] Examples of alkanedyl groups include methanediyl, ethane-1,2-diyl, propane-1,3-diyl, propane-1,2-diyl, and butane-1,4-diyl groups. Examples of alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, t-butyl, and pentyl groups.

[0066] As for the polymerizable monomer (b2), for example,

[0067] Alkoxyalkyl acrylates such as methoxymethylacrylate, 2-methoxyethylacrylate, ethoxymethylacrylate, 2-ethoxyethylacrylate, 4-methoxybutylacrylate, methoxypropylacrylate, ethoxypropylacrylate, propoxyethylacrylate, 2-butoxyethylacrylate, isobutoxyethylacrylate, etc.;

[0068] Glycol-based acrylates such as ethoxy-diethylene glycol acrylate, methoxy-triethylene glycol acrylate, and methoxy-dipropylene glycol acrylate;

[0069] ...can be cited.

[0070] ​Among these, alkoxyalkyl acrylates are preferred, and 2-methoxyethyl acrylate (MEA) is particularly preferred.

[0071] The structural unit (b-2) may be of type 1 or type 2 or more.

[0072] The structural unit (b-1) has a hydrophobic functional group, a phenyl group, which contributes to improving the water resistance (cracking resistance) of the antifouling film formed from the composition (I), as well as improving the film hardness, impact resistance, and combustibility. Although the reason for the improvement in combustibility is not clear, it is presumed that the structural unit (b-1) improves the film hardness of the antifouling film formed, thereby exhibiting physical combustibility against external forces such as frictional resistance in water.

[0073] The structural unit (b-2) contributes to the improvement of hydrophilicity of the antifouling film.

[0074] The copolymer (B) does not have structural units derived from silyl ester monomers.

[0075] When an acrylic copolymer without hydrolyzable groups is incorporated into a silyl ester polymer, the crack resistance of the coating film generally improves, while the antifouling properties tend to decrease. This is thought to be due to the fact that the side chains of the silyl ester polymer undergo a hydrolysis reaction in water to become a water-soluble polymer and are leached out, and the presence of an acrylic copolymer without hydrolyzable groups in the coating film inhibits the aforementioned hydrolysis reaction. Accordingly, it was thought that if a copolymer of styrene and a hydrophilic monomer is used as the acrylic copolymer, the balance between hydrophobicity and hydrophilicity of the antifouling coating film is improved, allowing for the simultaneous achievement of long-term antifouling properties and crack resistance. However, according to the inventors' investigation, it was found that such an effect is not necessarily achieved depending on the type of hydrophilic monomer.

[0076] As a result of further investigation by the inventors, it was found that by incorporating a copolymer of styrene and the aforementioned polymerizable monomer (b2), particularly MEA, into a silyl ester-based polymer, the balance between hydrophobicity and hydrophilicity of the antifouling film is particularly good, thereby enabling both long-term antifouling and crack resistance.

[0077] The ratio of structural unit (b-1) in copolymer (B) is preferably 30 mass% or more, more preferably 40 mass% or more, even more preferably 45 mass% or more, preferably 80 mass% or less, and more preferably 75 mass% or less. If the ratio of structural unit (b-1) is above the lower limit value, the water resistance (cracking resistance) of the antifouling film is high, which is desirable. If the ratio of structural unit (b-1) is below the upper limit value, the hydrophobicity of the antifouling film is not excessively high, and thus does not hinder the hydrolysis of polymer (A), resulting in excellent antifouling properties.

[0078] The ratio of structural unit (b-2) in the copolymer (B) is preferably 15 mass% or more, more preferably 20 mass% or more, preferably 45 mass% or less, more preferably 40 mass% or less. If the ratio of structural unit (b-2) is above the lower limit value, it is desirable for the antifouling properties of the antifouling film to be high. If the ratio of structural unit (b-2) is below the upper limit value, the hydrophilicity of the antifouling film is not excessively high, and since the antifouling agent is not leached into water in excess, it is desirable for the antifouling properties to be high not only for short-term (e.g., 12 months) but also for long-term (e.g., 36 months).

[0079] Recently, the service life of the antifouling film has been extended for a long period, such as 90 months. By using a copolymer (B) having structural unit (b-1) and structural unit (b-2), long-term antifouling properties and crack resistance of the antifouling film can be achieved. In particular, by keeping the ratio of structural unit (b-1) and structural unit (b-2) within the above range, the decrease in crack resistance of the antifouling film in the region where the ratio of structural unit (b-2) is high can be compensated for by the hydrophobicity of structural unit (b-1), thereby enabling long-term antifouling properties and crack resistance to be achieved.

[0080] In one embodiment of the copolymer (B), when the ratio of the structural unit (b-2) is 15 to 45 mass%, the antifouling properties are further improved compared to when the ratio of the structural unit (b-2) is less than 15 mass%, and the long-term antifouling properties are further improved compared to when the ratio of the structural unit (b-2) is greater than 45 mass%. In one embodiment of the copolymer (B), when the ratio of the structural unit (b-1) is 30 to 80 mass%, the crack resistance is further improved compared to when the ratio of the structural unit (b-1) is less than 30 mass%, and the antifouling properties are further improved compared to when the ratio of the structural unit (b-1) is greater than 80 mass%.

[0081] The ratio of each structural unit can be obtained by the same method as for polymer (A).

[0082] The copolymer (B) may additionally have a structural unit (b-3) derived from another ethylenically unsaturated monomer (hereinafter also referred to as “monomer (b3)”).

[0083] As for the monomer (b3), for example,

[0084] (Meta)acrylic acid;

[0085] (Meth)acrylic acid esters (except for polymerizable monomer (b2)), specifically, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3,5,5-trimethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, etc. Alkyl (meth)acrylates; aliphatic ring-containing (meth)acrylates such as cyclohexyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; methoxymethyl methacrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, 4-methoxybutyl methacrylate, methoxypropyl methacrylate, ethoxypropyl methacrylate, and propoxyethyl methacrylate. Alkoxyalkyl methacrylates or aryloxyalkyl (meth)acrylates such as 2-butoxyethyl methacrylate, isobutoxyethyl methacrylate, phenoxyethyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; glycol-based methacrylates such as ethoxy-diethylene glycol methacrylate, methoxy-triethylene glycol methacrylate, and methoxy-dipropylene glycol methacrylate; epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate;

[0086] Polyfunctional (meth)acrylates, specifically, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, di(trimethylolpropane)tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate;

[0087] Vinyl monomers, specifically, vinyl acetate, isobutyl vinyl ether, vinyltoluene, (meth)acrylonitrile, vinyl propionate, vinyl benzoate

[0088] ...can be cited.

[0089] Among these, (meth)acrylic acid esters are preferred, alkyl (meth)acrylates are more preferred, and methyl (meth)acrylates are even more preferred.

[0090] The structural unit (b-3) may be of type 1 or type 2 or more.

[0091] The proportion of structural unit (b-3) in the copolymer (B) is preferably 55 mass% or less, more preferably 45 mass% or less, and even more preferably 40 mass% or less, in the view that it does not impede the above effects by structural unit (b-1) and structural unit (b-2).

[0092] The weight average molecular weight (Mw) of the copolymer (B) is preferably 3,000 or more, more preferably 5,000 or more, even more preferably 7,000 or more, preferably 35,000 or less, more preferably 30,000 or less, and even more preferably 25,000 or less, in terms of improving the crack resistance of the antifouling film formed from the composition (I). Mw can be obtained by gel penetration chromatography (GPC) measurement under the conditions employed in the examples described below or by an equivalent method.

[0093] One or more types of copolymer (B) may be used.

[0094] The content ratio of the polymer (A) and the copolymer (B) in the composition (I) is preferably as follows. That is, the mass ratio (A:B) of the polymer (A) and the copolymer (B) is 90:10 to 30:70, more preferably 80:20 to 40:60, and even more preferably 75:25 to 45:55. This state is desirable because the long-term antifouling properties and crack resistance of the antifouling film are further improved.

[0095] The total content of polymer (A) and copolymer (B) is preferably 5 mass% or more, more preferably 10 mass% or more, and preferably 30 mass% or less, more preferably 20 mass% or less, with respect to 100 mass% of the total solid content of composition (I). If the total content is within this range, an antifouling film with excellent crack resistance can be easily obtained.

[0096] In addition, the content of solids in composition (I) is preferably 50 mass% or more, more preferably 65 mass% or more, and preferably 90 mass% or less, more preferably 85 mass% or less, from the perspective of making it a composition with excellent coating workability.

[0097] In addition, the solid content of composition (I) and its content in this specification are the heating residue (non-volatile content) and its content obtained by the following method or an equivalent method. Composition (I) was weighed and placed in a metal test dish of known mass, spread on the bottom surface, and placed in a constant temperature bath maintained at a temperature of 105 to 110°C for 3 hours. After removing it and cooling it to room temperature (e.g., 23°C), the mass was weighed again to determine the residue in the metal test dish. The content of the solid content (mass%) was calculated by the following formula.

[0098] Solid content percentage (mass%) = Remaining amount in metal test dish (g) × 100 / Mass of composition (I) taken by weighing (g)

[0099] The same applies to the solid content of each component and its content ratio.

[0100] <Method for manufacturing a polymer>

[0101] The method for manufacturing the polymer (A) and copolymer (B) is not particularly limited, but examples include solution polymerization, suspension polymerization, and pressure polymerization. For high versatility, solution polymerization performed under atmospheric pressure using a general organic solvent is preferred. As for the solution polymerization, the following steps may be used for manufacturing.

[0102] A solvent is placed in a reaction vessel equipped with a stirrer, a condenser, a thermometer, a dropping device, a nitrogen inlet tube, and a heating and cooling jacket, and heating and stirring are performed under a nitrogen stream at a temperature of about 60 to 200°C. While maintaining the same temperature, a mixture of each monomer and a polymerization initiator, and additionally, if necessary, a solvent and a chain transfer agent, is dropped from the dropping device in a ratio of the structural units described above, preferably, and a polymerization reaction is performed to obtain a polymer (A) or a copolymer (B).

[0103] There are no particular restrictions on the polymerization initiator, and various radical polymerization initiators may be used. Specifically, examples include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis-4-cyanovalvelotic acid, benzoyl peroxide, hydrogen peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxyoctoate, tert-butyl peroxybenzoate, potassium persulfate, sodium persulfate, etc. In addition, these radical polymerization initiators may be added to the reaction system only at the start of the reaction, or they may be added to the reaction system at both the start of the reaction and during the reaction.

[0104] The amount of polymerization initiator used in the manufacture of polymer (A) or copolymer (B) is preferably 0.1 to 20 parts by mass per 100 parts by mass of each monomer (reaction raw material), and more preferably 0.5 to 5 parts by mass.

[0105] Examples of solvents that can be used to manufacture polymer (A) or copolymer (B) include organic solvents and water. Examples of organic solvents include aromatic hydrocarbon solvents such as toluene, xylene, ethylbenzene, mesethylene, and coal tar naphtha; alcohol solvents such as ethanol, propanol, isopropyl alcohol, butanol, and isobutanol; ether solvents such as propylene glycol monomethyl ether and dipropylene glycol monomethyl ether; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, and cyclohexanone; and ester solvents such as ethyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate.

[0106] There are no particular restrictions on chain transfer agents, and examples include α-methylstyrene dimer, thioglycolic acid, diterpene, terpinolene, γ-terpinene; mercaptans such as tert-dodecyl mercaptan and n-dodecyl mercaptan; halides such as carbon tetrachloride, methylene chloride, bromoform, and bromotrichloroethane; and secondary alcohols such as isopropanol and glycerin.

[0107] When a chain transfer agent is used in the manufacture of a silyl ester-based polymer (A), the amount used is preferably 0.1 to 5 parts by mass per 100 parts by mass of each monomer (reaction raw material).

[0108] <Other ingredients>

[0109] The composition (I) may additionally contain one or more of the following as other components: a monocarboxylic acid compound (C), copper and / or copper compound (D), an organic antifouling agent (E), a coloring agent, a extender pigment, a thixotropic agent, a dehydrating agent, a plasticizer, a resin other than a polymer (A) and a copolymer (B), and a solvent.

[0110] Each of the ingredients described below may be used in one or two or more forms.

[0111] Monocarboxylic acid compound (C)

[0112] It is preferable that the composition (I) contains a monocarboxylic acid compound (C) in order to not only improve antifouling properties but also control the consumption rate of the coating film.

[0113] Examples of monocarboxylic acid compounds (C) include aliphatic or alicyclic monocarboxylic acids, their monocarboxylic acid derivatives, or their metal salts. Examples of monocarboxylic acid derivatives include esters and amides of monocarboxylic acids. Examples of metal salts include zinc salts, copper salts, aluminum salts, magnesium salts, calcium salts, and barium salts. Specific examples of monocarboxylic acids include rosins, naphthenic acids, cycloalkenylcarboxylic acids, bicycloalkenylcarboxylic acids, trimethylisobutenylcyclohexenecarboxylic acids, isononanolic acids, neodecanoic acids, versatic acids, stearic acids, hydroxystearic acids, palmitic acids, oleic acids, linoleic acids, linolenic acids, pyramic acids, abietic acids, and neobietic acids. Examples of rosins include, for instance, gum rosin, wood rosin, tall oil rosin, etc.; rosin derivatives such as hydrogenated rosin, disproportionated rosin, rosin metal salts, etc.; and pine tar. As for the monocarboxylic acid compound (C), rosin, rosin derivatives, naphthenic acid, versatic acid, trimethylisobutenylcyclohexenecarboxylic acid, and metal salts thereof are preferred.

[0114] The mass ratio of the monocarboxylic acid compound (C) in composition (I) (total mass of polymer (A) and copolymer (B): mass of monocarboxylic acid compound (C)) is preferably 95:5 to 40:60, more preferably 90:10 to 50:50.

[0115] Copper and / or copper compounds (D)

[0116] Composition (I) preferably contains copper and / or a copper compound (D) as an antifouling agent, with the view that it can further improve antifouling properties against aquatic organisms of animal species. Examples of copper include copper powder. Examples of copper compounds include cuprous oxide, copper thiocyanate, and cupronickel, and cuprous oxide and copper thiocyanate are preferred. Additionally, copper pyrithione is classified as an organic antifouling agent (E) below rather than a copper compound.

[0117] The content of copper and / or copper compound (D) is preferably 0.1 to 70 mass%, more preferably 1 to 60 mass%, based on 100 mass% of the total solid content of composition (I).

[0118] Organic Antifouling Agent (E)

[0119] It is preferable that the composition (I) contains an organic antifouling agent (E) as an antifouling agent. The organic antifouling agent (E) is a component that further improves the antifouling properties of the antifouling film.

[0120] As organic antifouling agents (E), examples include metal pyrithiones such as copper pyrithione and zinc pyrithione, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile, pyridinetriphenylborane, 4-isopropylpyridinediphenylmethylborane, N,N-dimethyl-N'-(3,4-dichlorophenyl)urea, N-(2,4,6-trichlorophenyl)maleimide, 2-methylthio-4-tert-butylamino-6-cyclopropylamino-1,3,5-triazine, medetomidine((+ / -)-4-[1-(2,3-dimethylphenyl)ethyl]-1H-imidazole), Examples include 2,4,5,6-tetrachloroisophthalonitrile, bisdimethyldithiocarbamoylzincethylenebisdithiocarbamate, chloromethyl-n-octyldisulfide, N',N'-dimethyl-N-phenyl-(N-fluorodichloromethylthio)sulfamide, N',N'-dimethyl-N-tolyl-(N-fluorodichloromethylthio)sulfamide, tetraalkylthiuramdisulfide, zinc dimethyldithiocarbamate, zinc ethylenebisdithiocarbamate, 2,3-dichloro-N-(2',6'-diethylphenyl)maleimide, 2,3-dichloro-N-(2'-ethyl-6'-methylphenyl)maleimide, etc. Among these, metal pyrithiones such as copper pyrithione and zinc pyrithione, medetomidine, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile, and bisdimethyldithiocarbamoylzinc ethylenebisdithiocarbamate are preferred, copper pyrithione, medetomidine, and 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one are more preferred, and copper pyrithione and medetomidine are even more preferred.

[0121] The content of the organic antifouling agent (E) is preferably 0.05 to 20 mass%, more preferably 0.1 to 10 mass%, based on 100 mass% of the total solid content of the composition (I).

[0122] "coloring agent"

[0123] Various conventionally known organic and inorganic pigments or dyes may be used as coloring agents. Examples of organic pigments include naphthol red and phthalocyanine blue. Examples of inorganic pigments include carbon black, Bengala, barite powder, titanium white (titanium oxide), and yellow iron oxide. It is preferable for composition (I) to contain a coloring agent so that the color of the antifouling film obtained from the composition can be arbitrarily controlled.

[0124] The content of the coloring agent is preferably 0.01 to 50 mass%, more preferably 0.01 to 30 mass%, based on 100 mass% of the total solid content of composition (I).

[0125] Constitutional Pigment

[0126] Examples of extender pigments include zinc oxide, talc, silica, mica, clay, potassium feldspar, calcium carbonate, kaolin, alumina white, white carbon, aluminum hydroxide, magnesium carbonate, barium carbonate, barium sulfate, and zinc sulfide. Among these, zinc oxide, talc, silica, mica, clay, calcium carbonate, kaolin, barium sulfate, and potassium feldspar are preferred.

[0127] Composition (I) preferably contains a extender pigment in order to improve the physical properties of the coating film, such as crack resistance, of the resulting antifouling film.

[0128] The content of the extender pigment is preferably 0.1 to 50 mass%, more preferably 1 to 40 mass%, based on 100 mass% of the total solid content of composition (I).

[0129] Yobyeonje

[0130] Thixotropic agents are components that contribute to the anti-sagging and anti-settling properties of paints.

[0131] Examples of thixotropic agents (anti-sagging agents, anti-sedimentation agents) include, for instance, salts selected from the group consisting of organic bentonite, amine salts, stearate salts, lecithin salts, and alkylsulfonates of Al, Ca, or Zn; waxes selected from the group consisting of polyethylene wax, polyethylene oxidized wax, amide wax, hydrogenated castor oil wax, and polyamide wax; and synthetic fine silica.

[0132] Thixotropic agents are used to prevent the sedimentation of solid materials such as copper and / or copper compounds (D), organic antifouling agents (E), colorants, extender pigments, and dehydrating agents during storage of antifouling paint compositions, or to improve workability during painting.

[0133] The content of the thixotropic agent is preferably 0.1 to 20 mass%, more preferably 0.1 to 10 mass%, based on 100 mass% of the total solid content of composition (I).

[0134] Dehydration agent

[0135] Examples of dehydrating agents include inorganic dehydrating agents and organic dehydrating agents. Examples of inorganic dehydrating agents include synthetic zeolite, anhydrous gypsum, and hemihydrate gypsum. Examples of organic dehydrating agents include alkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetrabutoxysilane, tetraphenoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, and trimethylethoxysilane, or polyalkoxysilanes which are condensates thereof, and alkyl orthoformate esters such as methyl orthoformate and ethyl orthoformate. Dehydrating agents are used for purposes such as preventing gelation caused by the decomposition of hydrolyzable resins due to moisture generated during the manufacture and / or storage of antifouling paint compositions.

[0136] The content of the dehydrating agent is preferably 0.01 to 10 mass%, more preferably 0.1 to 5 mass%, based on 100 mass% of the total solid content of composition (I).

[0137] Plasticizer

[0138] Examples of plasticizers include n-paraffin, chlorinated paraffin, petroleum resin, ketone resin, tricresyl phosphate, polyvinyl ethyl ether, and dialkyl phthalate, among which chlorinated paraffin, petroleum resin, and ketone resin are preferred. It is preferable that composition (I) contains a plasticizer in that the crack resistance and water resistance of the antifouling film obtained from the composition are further improved.

[0139] Chlorinated paraffin may have either a straight-chain or branched molecular structure, and may be in a liquid or solid (powder) state under room temperature conditions.

[0140] In addition, the average number of carbon atoms in the chlorinated paraffin is preferably 8 to 30, and more preferably 10 to 26 per molecule. An antifouling paint composition containing such chlorinated paraffin can form an antifouling film with minimal cracking or peeling. Furthermore, it is preferable that the average number of carbon atoms be 8 or more, as this provides a high effect in inhibiting cracking, whereas the average number of carbon atoms be 30 or less, as this does not inhibit antifouling properties.

[0141] In addition, the viscosity of the chlorinated paraffin (unit poise, measurement temperature 25°C) is preferably 1 or higher, more preferably 1.2 or higher, and the specific gravity (25°C) is preferably 1.05 to 1.80 g / cm³, more preferably 1.10 to 1.70 g / cm³.

[0142] Examples of petroleum resins include C5-based, C9-based, styrene-based, and dicyclopentadiene-based resins, or their hydrogenated derivatives.

[0143] The content of the plasticizer is preferably 0.01 to 10 mass%, more preferably 0.1 to 5 mass%, based on 100 mass% of the total solid content of composition (I).

[0144] Resins other than polymer (A) and copolymer (B)

[0145] The composition (I) may contain resins other than the aforementioned polymer (A) and copolymer (B). Examples of such resins include non-water-soluble or water-repellent resins such as polyester resin, unsaturated polyester resin, fluoropolymer, polybutene resin, polyurethane resin, epoxy resin, polyamide resin, vinyl resin (vinyl chloride copolymer, ethylene-vinyl acetate copolymer, etc.), chlorinated olefin resin, styrene-butadiene copolymer resin, alkyd resin, coumarone resin, terpene phenol resin, silicone rubber, and chlorinated rubber.

[0146] The content of the above resins is, for example, 0.01 to 100 parts by mass with respect to 100 parts by mass of the total of the polymer (A) and copolymer (B).

[0147] "solvent"

[0148] Composition (I) may contain a solvent, such as water or an organic solvent, as needed to improve the dispersibility of each component or to adjust the viscosity of the composition. The solvent may be the solvent used when preparing the polymer (A) or copolymer (B), or it may be a solvent separately added when preparing an antifouling paint composition by mixing the polymer (A) and copolymer (B) with other components as needed. An organic solvent is preferred as the solvent. Examples of organic solvents include the organic solvents described in the item <Method for manufacturing polymer>.

[0149] When composition (I) contains a solvent, the amount of the solvent is determined according to the desired viscosity based on the application form of the paint composition. The amount of solvent in composition (I) is preferably 5 to 50 mass%, more preferably 10 to 40 mass%. If the amount of solvent is excessively high, it may cause problems such as a decrease in anti-sagging properties.

[0150] <Method for Manufacturing an Antifouling Paint Composition>

[0151] Composition (I) can be prepared by appropriately utilizing known methods, except for the use of a polymer (A) and a copolymer (B). For example, the polymer (A), the copolymer (B), and, if necessary, the other components may be added to a stirring vessel at once or in any order, and each component may be mixed using known stirring and mixing means and dispersed or dissolved in a solvent.

[0152] As means for stirring and mixing, examples include using a paint shaker, high-speed disperser, sand grind mill, basket mill, ball mill, three-roll, loss mixer, planetary mixer, and universal Shinagawa stirrer.

[0153] [Uses of Antifouling Paint Compositions]

[0154] The antifouling film of the present embodiment (hereinafter also referred to as "antifouling film (J)") is formed from the composition (I). The antifouling film-attached substrate of the present embodiment (hereinafter also referred to as "antifouling substrate (K)") comprises a substrate and an antifouling film (J) installed on the surface of said substrate.

[0155] A method for manufacturing an antifouling material (K) comprises a process of applying or impregnating a composition (I) onto a substrate (object, object to be coated), and, if the composition (I) contains a solvent, further comprises a process of drying the coated or impregnated body obtained by applying or impregnating the composition onto the substrate.

[0156] For application, known methods such as air spray, airless spray, brush, and roller can be used.

[0157] The composition (I) coated or impregnated by the above-described method can be dried by leaving it for, for example, under conditions of -5 to 30°C, preferably for about 1 to 10 days, more preferably for about 1 to 7 days, to obtain an antifouling film (J). In addition, the drying of the composition (I) may be carried out while blowing air under heating.

[0158] Alternatively, the antifouling material (K) can also be manufactured by forming an antifouling film (J) from the composition (I) on the surface of a temporary material, peeling the antifouling film (J) from the temporary material, and attaching it to a material to be antifouled. In this case, the antifouling film (J) may be attached to the material through an adhesive layer.

[0159] The surface of the substrate may be primer-treated, or the surface may have a layer formed from various resin-based paints such as epoxy resin-based paint, vinyl resin-based paint, acrylic resin-based paint, or urethane resin-based paint. In this case, the surface of the substrate on which the antifouling film (J) is installed refers to the surface after primer treatment or the surface of the layer formed from the above paint.

[0160] Although there are no particular limitations on the materials used, composition (I) is preferably used for long-term antifouling of materials in a wide range of industrial fields such as ships, fisheries, and underwater structures. For this reason, materials used may include, for example, ships (e.g., large steel vessels such as container ships and tankers, fishing boats, FRP boats, wooden boats, yachts, etc., including both newly built and repaired vessels), underwater structures (e.g., oil pipelines, water supply pipes, circulating water pipes, water supply and drainage pipes for factories and thermal / nuclear power plants, submarine cables, seawater utilization equipment (seawater pumps, etc.), megafloats, coastal roads, undersea tunnels, port facilities, various underwater civil engineering structures in canals and waterways, etc.), fishing materials (e.g., ropes, fishing nets, fishing gear, buoys, buoys), water supply and drainage pipes for seawater in factories and thermal / nuclear power plants, etc., diving suits, goggles, oxygen cylinders, swimsuits, torpedoes, etc. Among these, ships, underwater structures, fishing materials, and water supply and drainage pipes are preferred, ships and underwater structures are more preferred, and ships are particularly preferred.

[0161] In manufacturing the antifouling material (K), if the material is a fishing net or a steel plate, the composition (I) may be applied directly to the surface of the material, and if the material is a fishing net, the composition (I) may be impregnated into the surface thereof. Also, if the material is a steel plate, a base material such as a rust inhibitor or a primer may be applied to the surface of the material in advance to form a base layer, and then the composition (I) may be applied to the surface of the base layer. Additionally, for the purpose of repair, an antifouling film (J) may be additionally formed on the surface of a material on which an antifouling film (J) or a conventional antifouling film is formed, such as a steel plate having a deteriorated antifouling film.

[0162] The thickness of the antifouling film (J) is not particularly limited, but, for example, is about 30 to 1,000 μm. In addition, when the antifouling film (J) is formed by applying the composition (I) onto a substrate, the thickness of the antifouling film (J) formed in one application is preferably 10 to 300 μm, more preferably 30 to 200 μm, and the method of applying it one to multiple times may be used.

[0163] A vessel equipped with an antifouling film (J) can prevent the attachment of aquatic organisms, thereby preventing a decrease in vessel speed and an increase in fuel efficiency. An underwater structure equipped with an antifouling film (J) can maintain its function for a long period of time because it can prevent the attachment of aquatic organisms over a long period. A fishing net equipped with an antifouling film (J) can prevent the clogging of the mesh openings because it can prevent the attachment of aquatic organisms. Furthermore, a water supply and drainage pipe having an antifouling film (J) on its inner surface can prevent the clogging of the water supply and drainage pipe and a decrease in water flow velocity because it can prevent the attachment and proliferation of aquatic organisms.

[0164] Examples

[0165] The present invention is described in more detail below based on examples and comparative examples, but the present invention is not limited in any way to the examples below. In addition, in the examples and comparative examples below, "parts" indicates "parts by mass".

[0166] [Measurement Conditions]

[0167] Gel penetration chromatography (GPC) measurements were performed on the polymer, and the content of the heating residue was measured on the copolymer solution. The conditions for each measurement are as follows.

[0168] <GPC Measurement Conditions>

[0169] Device: "HLC-8320GPC" (Manufactured by Dosho Co., Ltd.)

[0170] Column: "TSKgel guardcolumn Super MP(HZ)-M + TSKgel Super Multipore HZ-M + TSKgel Super Multipore HZ-M" (All manufactured by Dosho Co., Ltd.)

[0171] Eluent: Tetrahydrofuran (THF)

[0172] Flow rate: 0.35 ml / min

[0173] Detector: RI

[0174] Column constant temperature: 40℃

[0175] Calibration curve: Standard polystyrene and styrene monomers

[0176] Sample preparation method: The copolymer solution obtained in each preparation example was diluted by adding THF, and the filtrate obtained by filtering with a membrane filter was used as a GPC measurement sample.

[0177] <Conditions for Measuring Residue Content>

[0178] A copolymer solution was weighed and placed in a metal test dish of known mass, spread on the bottom surface, and heated in a constant temperature bath maintained at 105–110°C for 3 hours. After removing it and cooling it to room temperature, the mass was weighed again to determine the remaining amount in the metal test dish. The solid content (mass%) was calculated using the following formula.

[0179] Solid content percentage (mass%) = Remaining amount in metal test dish (g) × 100 / Mass of copolymer solution taken by weighing (g)

[0180] [Example of polymer preparation]

[0181] [Preparation Example 1] Preparation of a solution of a silyl ester-based polymer (A)

[0182] 43 parts xylene and 10 parts triisopropylsilyl methacrylate were placed in a reaction vessel equipped with a stirrer, condenser, thermometer, nitrogen inlet tube, and a dropping device, and heating and stirring were performed under a nitrogen atmosphere until the liquid temperature reached 80°C. While maintaining the same conditions, a mixture of monomers (50 parts triisopropylsilyl methacrylate, 25 parts 2-methoxyethyl methacrylate, 10 parts methyl methacrylate, 5 parts butyl acrylate) and a polymerization initiator (1.35 parts 2,2'-azobis(isobutyronitrile)) was dropped into the reaction vessel from the dropping device over a period of 2 hours. Subsequently, heating and stirring were continued for 1 hour at the same temperature and for 1 hour at a liquid temperature of 88°C, after which the liquid temperature was raised to 95°C. While maintaining the same temperature, 0.1 parts of 2,2'-azobis(isobutyronitrile) were added a total of four times at 30-minute intervals, and then the liquid temperature was raised to 105°C. After continuing heating and stirring for 30 minutes at the same temperature, 23.7 parts of xylene were added to the reaction vessel to obtain a solution of the silyl ester copolymer (A-1) (copolymer solution (A-1)). The weight average molecular weight of the silyl ester copolymer (A-1) was 28,649. The content of the heating residue of the above solution was 60.0 mass%.

[0183] [Preparation Example 2] Preparation of a solution of copolymer (B)

[0184] 66.7 parts of xylene were placed in a reaction vessel equipped with a stirrer, a condenser, a thermometer, a nitrogen inlet tube, and a dropping device, and heating and stirring were performed under a nitrogen atmosphere until the liquid temperature reached 110°C. While maintaining the same conditions, a mixture of monomers (70 parts styrene, 30 parts 2-methoxyethyl acrylate) and a polymerization initiator (4 parts 2,2'-azobis(isobutyronitrile), 1 part tert-butylperoxybenzoate) was dropped into the reaction vessel from the dropping device over a period of 3 hours, and then heating and stirring were continued for 1 hour at the same temperature, 1 hour at 120°C, and 1 hour at 130°C to obtain a solution of copolymer (B-1) (copolymer solution (B-1)).

[0185] By changing the monomers as described in Table 1 and performing the same operation as above while appropriately adjusting the liquid temperature and the amount of polymerization initiator, solutions of copolymer (B) (copolymer solution (B-2) to copolymer solution (B-14)) and solutions of control copolymer (cB) (copolymer solution (cB-1) to copolymer solution (cB-7)) were obtained.

[0186] The properties are shown in Table 1. The values ​​for monomers represent the mixing amount (parts by mass).

[0187] The content of the heating residue of the above solution was approximately 60 mass%.

[0188] St: Styrene

[0189] MMA: Methyl methacrylate

[0190] BA:n-butyl acrylate

[0191] MEA: 2-methoxyethyl acrylate

[0192] MEMA: 2-methoxyethyl methacrylate

[0193] HEA: 2-hydroxyethyl acrylate

[0194] HPA: 2-hydroxypropyl acrylate

[0195] GMA: Glycidyl methacrylate

[0196] PhOEtA: 2-phenoxyethyl acrylate

[0197]

[0198] [Preparation of Antifouling Paint Composition]

[0199] [Example 1]

[0200] An antifouling paint composition was prepared as follows.

[0201] 11.3 parts xylene, 1 part aromatic hydrocarbon mixture (Solvesso 150), 4 parts gum rosin (China Gum Rosin WW), 0.5 parts alkoxysilane (ethylsilicate 28), 12 parts silyl ester copolymer solution (A-1), and 8 parts copolymer solution (B-1) were added to a plastic container and mixed using a paint shaker until each component was uniformly dispersed or dissolved. Subsequently, 7 parts of talc (FC-1), 7 parts of zinc oxide (zinc oxide type 3), 9.5 parts of barium sulfate (precipitated barium sulfate 100), 35 parts of cuprous oxide (NORDOX), 0.7 parts of red Bengala (TODA COLOR NM-50), 1 part of titanium oxide (Taifake R-930), 1 part of copper pyrithione (Copper Omadine Powder), 1 part of polyethylene oxide (Disparon 4200-20X), and 150 parts of glass beads were added to a plastic container and the components were dispersed by stirring with a paint shaker for 1 hour. After dispersion, 1 part of fatty acid amide (Disparon A630-20X) was added and stirred with a paint shaker for 20 minutes, after which the glass beads were removed from the mixture using a filter screen (mesh size: 80 mesh) to obtain an antifouling paint composition.

[0202] [Examples 2–20]

[0203] An antifouling paint composition was prepared in the same manner as Example 1, except that the type and amount of each component were changed as shown in Table 2.

[0204] [Comparative Examples 1–7]

[0205] An antifouling paint composition was prepared in the same manner as Example 1, except that the type and amount of each component were changed as shown in Table 3.

[0206] (A), (B), and (cB) in Tables 2 and 3 are the amounts of copolymer solution.

[0207] [Evaluation of Physical Properties of Antifouling Paint Composition]

[0208] The physical properties of the coating film formed using the antifouling paint compositions obtained in the examples and comparative examples were evaluated as follows. The results obtained are shown in Tables 2 and 3.

[0209] <Political Anti-Fouling Test>

[0210] An epoxy-based anti-corrosion paint (product name "Banno 500", manufactured by Chugoku Paint Co., Ltd.) was applied using an air spray onto a sandblasted steel plate (300 mm × 100 mm × 2.3 mm) to a dry film thickness of 150 μm, and a cured film was formed by drying at 23°C for one week. Subsequently, a vinyl-based binder paint (product name "Silbox SQ-K", manufactured by Chugoku Paint Co., Ltd.) was applied using an air spray onto the cured film to a dry film thickness of 40 μm, and the film was dried at 23°C for 24 hours.

[0211] Next, each antifouling paint composition prepared in the example or comparative example was applied to the surface of the dried film formed from the vinyl binder paint to a dry film thickness of 200 μm, and then dried at 23°C for 7 days to form an antifouling film, thereby producing a stationary antifouling test plate.

[0212] A stationary antifouling test plate was prepared and suspended and immersed in the Seto Inland Sea off the coast of Hatsukaichi City, Hiroshima Prefecture, at a depth of 400 mm or less from the water surface, and after 6, 12, 24, and 36 months from the start of immersion, the area of ​​the part where aquatic organisms are attached to the antifouling film (hereinafter also referred to as "attachment area") (%) was measured when the total area of ​​the antifouling film on the part of the test plate that is constantly submerged in seawater was set to 100%, and the stationary antifouling performance was evaluated based on the evaluation criteria below.

[0213] (Evaluation Criteria)

[0214] 5: The attachment area is less than 5%.

[0215] 4: The attachment area is 5% or more and less than 20%.

[0216] 3: The attachment area is 20% or more and less than 50%.

[0217] 2: The attachment area is 50% or more and less than 70%.

[0218] 1: The attachment area is 70% or more.

[0219] <Coating Film Crack Resistance (Water Resistance) Test>

[0220] An epoxy-based anti-corrosion paint (product name "Banno 500", manufactured by Chugoku Paint Co., Ltd.) was applied using an air spray onto a sandblasted steel plate (150 mm × 70 mm × 1.6 mm) to a dry film thickness of 150 μm, and a cured film was formed by drying at 23°C for one week. Subsequently, a vinyl-based binder paint (product name "Silbox SQ-K", manufactured by Chugoku Paint Co., Ltd.) was applied using an air spray onto the cured film to a dry film thickness of 40 μm, and the film was dried at 23°C for 24 hours.

[0221] Next, each antifouling paint composition prepared in the example or comparative example was applied to the surface of the dried film formed from the vinyl binder paint to a dry film thickness of 300 μm, and then dried at 23°C for 7 days to form an antifouling film, thereby producing a test plate.

[0222] The above test plate was immersed in artificial seawater at 50°C, and the appearance of the coating film was inspected every month for six months. In addition, the artificial seawater was replaced with fresh water every week. The crack resistance of the coating film was evaluated based on the following evaluation criteria (i.e., the ratio of the crack area to the total surface area of ​​the coating film).

[0223] (Evaluation Criteria)

[0224] 5: Cases where there are no abnormalities at all.

[0225] 4: Cracks are found in less than 10% of the total surface area of ​​the coating film.

[0226] 3: Cracks are detected in more than 10% and less than 30% of the total surface area of ​​the coating film.

[0227] 2: Cracks are detected in more than 30% and less than 50% of the total surface area of ​​the coating film.

[0228] 1: Cracks are confirmed to occur on more than 50% of the entire surface area of ​​the coating film.

[0229]

[0230]

[0231] In addition, the details of the components used in the examples and comparative examples are as follows.

[0232]

[0233] When copolymers containing HEA or HPA units were used instead of MEA units, antifouling and crack resistance were exhibited in the short term, but were low in the long term. This is presumed to be due to the excessively high hydrophilicity of HEA and HPA compared to MEA.

[0234] When copolymers containing GMA units instead of MEA units were used, long-term antifouling performance tended to be low. This is presumed to be due to the lower hydrophilicity of GMA units compared to MEA units, which leads to insufficient hydrolysis of silyl ester-based polymers.

[0235] When a copolymer containing MEMA units was used instead of MEA units, the antifouling performance was low. This is presumed to be due to the fact that MEMA units have higher hydrophobicity compared to MEA units, which inhibits the hydrolysis reaction of silyl ester-based polymers.

[0236] When a copolymer having MMA or BA units was used instead of St units, the antifouling and crack resistance were low.

[0237] Compared to the comparative examples above, when a copolymer having St and MEA units was used, long-term antifouling and crack resistance were excellent. Although the reason is not clear, it is presumed that the balance between hydrophobicity and hydrophilicity of the antifouling film was particularly well achieved by incorporating the St and MEA copolymer into a silyl ester-based polymer.

Claims

Claim 1 An antifouling paint composition comprising a silyl ester-based polymer (A) having a structural unit (a-1) derived from a polymerizable monomer (a1) represented by the formula (a1) below, a copolymer (B) having a structural unit (b-1) derived from styrene, and a structural unit (b-2) derived from a polymerizable monomer (b2) represented by the formula (b2). [Equation (a1), R 1 is a hydrogen atom or a methyl group, and R 2 ~R 6 is a monovalent organic group having 1 to 20 carbon atoms that may each independently possess a heteroatom, and X is a hydrogen atom or R 7 The unit represented by ―O―C(=O)― (R 7 A hydrogen atom, a monovalent organic group having 1 to 20 carbon atoms that may have heteroatoms, or R 8 R 9 R 10 A silyl group (R represented by Si-) 8 , R 9 and R 10 Each is a monovalent organic group having 1 to 20 carbon atoms that may independently possess a heteroatom.) and n is an integer greater than or equal to 0 or 1.] Formula (b2): CH2=CH―COO―(R b1 ―O) n ―R b2 [Equation (b2), R b1 is an alkanedial group having 1 to 5 carbon atoms, and R b2 is an alkyl group having 1 to 5 carbon atoms, and n is an integer from 1 to 3. Claim 2 An antifouling paint composition according to claim 1, wherein the proportion of the structural unit (b-1) in the copolymer (B) is 30 to 80 mass%. Claim 3 An antifouling paint composition according to claim 1, wherein the proportion of the structural unit (b-2) in the copolymer (B) is 15 to 45 mass%. Claim 4 An antifouling paint composition according to claim 1, wherein the proportion of the structural unit (b-1) in the copolymer (B) is 30 to 80 mass%, and the proportion of the structural unit (b-2) is 15 to 45 mass%. Claim 5 An antifouling paint composition according to claim 1, wherein the polymerizable monomer (b2) represented by formula (b2) is an alkoxyalkyl acrylate. Claim 6 An antifouling paint composition according to claim 5, wherein the polymerizable monomer (b2) represented by formula (b2) is 2-methoxyethyl acrylate. Claim 7 An antifouling paint composition according to claim 1, wherein the polymerizable monomer (a1) is triisopropylsilyl methacrylate. Claim 8 An antifouling paint composition according to claim 1, wherein the mass ratio (A:B) of the silyl ester-based polymer (A) and the copolymer (B) is 90:10 to 30:

70. Claim 9 An antifouling paint composition according to claim 1, further containing a monocarboxylic acid compound (C). Claim 10 An antifouling paint composition according to claim 1, further containing copper and / or a copper compound (D). Claim 11 An antifouling paint composition according to claim 1, further containing an organic antifouling agent (E). Claim 12 An antifouling film formed from an antifouling paint composition described in any one of claims 1 to 11. Claim 13 A substrate and an antifouling film attached substrate having the antifouling film described in claim 12 installed on the surface of the above substrate. Claim 14 In Clause 13, the above-mentioned antifouling coating attached material is one or more types selected from ships, underwater structures, fishing materials, and water supply and drainage pipes. Claim 15 A method for manufacturing a substrate with an antifouling film attached, comprising a process of applying or impregnating a substrate with an antifouling paint composition described in any one of claims 1 to 11.

Citation Information

Patent Citations

  • Antifouling coating composition, antifouling coating film, antifouling substrate, and method for producing antifouling substrate

    KR1020160137382A

  • Antifouling coating composition, antifouling coating film, non-fouling base, process for producing non-fouling base, and method for storing antifouling coating composition

    KR1020170100671A

  • Antifouling coating composition, coating film, and coating-film-attached base material

    KR1020180091926A

  • Antifouling paint composition, antifouling paint film, antifouling substrate, and method for manufacturing antifouling substrate

    KR1020150138354A